1974
DOI: 10.1073/pnas.71.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 5-Oxoproline from Glutathione in Erythrocytes by the γ-Glutamyltranspeptidase-Cyclotransferase Pathway

Abstract: -y-Glutamyltranspeptidase activity was demonstrated in the membrane fraction of rabbit erythrocytes. The activity observed (with glutathione and various amino-acid acceptors) was similar in magnitude to that of the -y-glutamylcyclotransferase and -y-glutamylcysteine synthetase activities found in the soluble fraction of the cell. No transpeptidase activity was observed with either -y-glutamyl p-nitroanilide or oxidized glutathione in contrast to the rabbit-kidney enzyme for which these compounds and glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 29 publications
4
16
0
1
Order By: Relevance
“…Although GGCT was first purified nearly 40 years ago (Board et al, 1978; Orlowski et al, 1969; Palekar et al, 1974), the gene encoding this enzyme has only recently been identified (Oakley et al, 2008). It shares sequence and structural similarity to γ-glutamylamine cyclotransferase, which degrades γ-glutamyl-ɛ-lysine liberated from proteins covalently crosslinked by transglutaminases (Oakley et al, 2010).…”
Section: Glutathione Salvagementioning
confidence: 99%
See 1 more Smart Citation
“…Although GGCT was first purified nearly 40 years ago (Board et al, 1978; Orlowski et al, 1969; Palekar et al, 1974), the gene encoding this enzyme has only recently been identified (Oakley et al, 2008). It shares sequence and structural similarity to γ-glutamylamine cyclotransferase, which degrades γ-glutamyl-ɛ-lysine liberated from proteins covalently crosslinked by transglutaminases (Oakley et al, 2010).…”
Section: Glutathione Salvagementioning
confidence: 99%
“…Initial studies by Meister and co-workers indicated that GGCT purified from rat liver has relatively broad substrate specificity, consistent with the relatively non-specific transfer of a γ-glutamyl moiety to acceptor substrates by GGT. These observations led to the proposal of a GGT/GGCT pathway for import of amino acids, as a component function of the γ-glutamyl cycle (Orlowski et al, 1969; Palekar et al, 1974). However, GGCT involvement in amino acid salvage has not been directly demonstrated using systems in which enzyme expression has been experimentally altered.…”
Section: Glutathione Salvagementioning
confidence: 99%
“…The effluent was lyophilized and then the material was dissolved in distilled water and fractionated on Dowex-1 (formate) according to Wilk and Orlowski (20). The oxoproline-containing fraction was lyophilized and repurified by paper chromatography (21). The 5-oxoproline was then converted to L-glutamic acid and assayed with glutamic dehydrogenase (EC 1.4.1.3) (5).…”
Section: Introductionmentioning
confidence: 99%
“…These results show that carboxylic acid units in the alanine and glutaryl terminals are important for the inhibition. Ring-containing substrates 8 to 10 were only minimally effective, showing at best only 20% inhibition (entries 7,8,9). Compounds with mono and dimethyl groups substituents at the 2-position, 11 (49%) and 13 (52%), showed 2-7 times greater inhibitory activity than those located at the 4-position, 12 (23%) and 14 (7%) in entries 10-13.…”
mentioning
confidence: 99%